2012
DOI: 10.1016/j.jup.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the technical efficiency of airports in Latin America

Abstract: Relying on a unique dataset this paper uses Data Envelopment Analysis methods to compute an efficient production frontier for a representative sample of Latin American airports. Latin America has implemented a wide variety of private sector participation schemes in the airport sector since the late 90s. To assess whether privately operated airports had higher rates of total factor productivity growth than public airports we compute Malmquist indexes for the period [2000][2001][2002][2003][2004][2005][2006][200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Esto puede deberse a la falta de información pública. Sin embargo, como análisis de conjunto de aeropuertos, aparece un estudio en el que son analizados 21 aeropuertos en el período 2000-2007 [20]. …”
Section: Revista Ingenierías Universidad De Medellínunclassified
See 1 more Smart Citation
“…Esto puede deberse a la falta de información pública. Sin embargo, como análisis de conjunto de aeropuertos, aparece un estudio en el que son analizados 21 aeropuertos en el período 2000-2007 [20]. …”
Section: Revista Ingenierías Universidad De Medellínunclassified
“…De la misma forma se confirma en el estudio de [20] cuyos resultados indican que, para el caso de 21 aeropuertos latinoamericanos, los aeropuertos operados de forma privada se desempeñan mejor, en promedio, que los aeropuertos públicos.…”
Section: Dea Domney Et Al 2005unclassified
“…More widely, there has been some research which points to the fact that privately-operated airports in Latin America have not outperformed publicly operated ones (Perelman & Serebrisky, 2010) and that changes in productivity were largely due to adapting well known technologies and production processes. Vogel (2006) concluded that public airports may better be able to capitalise on their government backing, giving them greater ability to assume higher leverage in the financing of productive assets.…”
Section: Divestment Policies and The Australian Contextmentioning
confidence: 99%
“…The other sectors were also analysed by means of the bootstrapped Malmquist indices. For instance, Perelman and Serebrisky (2012) analysed the efficiency and productivity of Latin American airports. Jaraitė and Di Maria (2012) employed the bootstrapped Malmquist indices for analysis of power generation in the European Union.…”
Section: Introductionmentioning
confidence: 99%